(3GdfeGPL GdQjGVjI hCSGdjH GdJMdjd Gdcej aj GdJNWjW GdMVQj hGdEbdjej (B/s - (3GdYGfj, eMeO LGSe eMeO Ydj TYHGfs ((3YeGf(B: s (3OGQ UaGA(B, s, 2005)
(3OhQ GdfeGPL aj GdYedjI GdJNWjWjI heHGOF GdJUeje hGSJYeGd GdfeGPL(B-(3eHGOF GdQjGVjI hGdfeGPL GdNWjI hGdLGPHjI(B-(3GdESJfJGLGJs
(3GdJhVjMGJ HGddZI GdCfLdjRjIs
Keywords: (3GdYedjI GdJNWjWjIs; (3GdfeGPLs; (3GdfeGPL GdEKHGJjIs; (3GdfeGPL GdJNWjWjIs; (3GdfeGPL GdhUajIs